Genetic characterization of hepatitis E virus from wild boar in China. Issue 5 (30th June 2022) - Gong, Wenjie; Du, Haiying; Sun, Xuefei; Sun, Heting; Peng, Peng; Qin, Siyuan; Geng, Haidong; Zeng, Zheng; Liang, Wangwang; Ling, Hongquan; Tu, Changchun; Tu, Zhongzhong
Abstract: Hepatitis E virus (HEV), the causative agent of hepatitis E (HE), is classified into four major genotypes (1–4), with wild boar being the main natural reservoir for genotypes 3 and 4. However, little is known about the prevalence of HEV infection in wild boars in China. In this study, RT‐nested PCR and RT‐quantitative PCR were used to detect the HEV RNA in tissue samples taken from 331 free‐ranging wild boars collected between 2018 and 2020 from 24 regions across China, and the partial ORF2 genes or complete genomes of the positive samples were sequenced. Furthermore, antibodies against HEV in 216 serum samples from wild boars were tested by ELISA. As a result, HEV RNA was detected in nine out of 331 liver samples of wild boars (2.72%), which were distributed in eight regions. Genetic and evolutionary analysis of partial ORF2 sequences indicated that the HEV strains identified in this study share 83.9%–100% nucleotide sequence identity and belong to subtypes 4d ( n  = 6), 4g ( n  = 2), and 4h ( n  = 1), and similar phylogeny was obtained using the complete genome sequences of seven wild boar HEV strains. Additionally, the HEV viral loads were higher in the liver than in other tissues and blood. Moreover, 61 out of 216 sera (28.2%) from wild boars tested positive for anti‐HEV antibodies. To our knowledge, this is the first study to report the epidemiological situations of HEV infections in free‐ranging wild boars in China, and the obtained data are valuable for prevention and control of HE.